Role of pytochromes P450 1A1/2 in detoxication and activation of carcinogenic aristolochic acid I: studies with the hepatic NADPH:Cytochrome P450 reductase null (HRN) mouse model - Levová, Kateřina; Moserová, Michaela; Kotrbová, Věra; Šulc, Miroslav; Henderson, Colin J.; Wolf, C. Roland; Phillips, David H.; Frei, Eva; Schmeiser, Heinz; Mareš, Jaroslav; Arlt, Volker M.; Stiborová, Marie (Toxicological sciences, 2011)
Aristolochic acid (AA) causes aristolochic acid nephropathy, Balkan endemic nephropathy, and their urothelial malignancies. To identify enzymes involved in the metabolism of aristolochic acid I (AAI), the major toxic component of AA we used HRN (hepatic cytochrome P450 [Cyp] reductase null) mice, in which NADPH:Cyp oxidoreductase (Por) is deleted in hepatocytes. AAI was demethylated by hepatic Cyps in vitro to 8-hydroxy-aristolochic acid I (AAIa), indicating that less AAI is distributed to extrahepatic organs in wild-type (WT) mice. Indeed, AAI-DNA-adduct levels were significantly higher in organs of HRN mice, having low hepatic AAI demethylation capacity, than in WT mice. Absence of AAI demethylation in HRN mouse liver was confirmed in vitro; hepatic microsomes from WT, but not from HRN mice, oxidized AAI to AAIa. To define the role of hepatic Cyps in AAI demethylation, modulation of AAIa formation by CYP inducers was investigated. We conclude that AAI demethylation is attributable mainly to Cyp1a1/2. The higher AAI-DNA adduct levels in HRN than WT mice were the result of the lack of hepatic AAI demethylation concomitant with a higher activity of cytosolic NAD(P)H:quinone oxidoreductase (Nqo1), which activates AAI. Mouse hepatic Cyp1a1/2 also activated AAI to DNA adducts under hypoxic conditions in vitro, but in renal microsomes, Por and Cyp3a are more important than Cyp1a for AAI-DNA adduct formation. We propose that AAI activation and detoxication in mice are dictated mainly by AAI binding affinity to Cyp1a1/2 or Nqo1, by their turnover, and by the balance between oxidation and reduction of AAI by Cyp1a.
Gesehen am 19.08.2022